2021
DOI: 10.1002/ehf2.13488
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal P‐wave terminal force in lead V1 is a marker for atrial electrical dysfunction but not structural remodelling

Abstract: Aims There is a lack of diagnostic and therapeutic options for patients with atrial cardiomyopathy and paroxysmal atrial fibrillation. Interestingly, an abnormal P-wave terminal force in electrocardiogram lead V 1 (PTFV 1 ) has been associated with atrial cardiomyopathy, but this association is poorly understood. We investigated PTFV 1 as a marker for functional, electrical, and structural atrial remodelling. Methods and results Fifty-six patients with acute myocardial infarction and 13 kidney donors as contro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 29 publications
(84 reference statements)
1
27
1
Order By: Relevance
“…The LV EF was mildly reduced in both groups but worse in patients with abnormal PTFV 1 (43.15 ± 11.51% vs. 48.93 ± 7.45%, p = 0.035). Interestingly, volumetric parameters for LA size and function, such as LA fractional area change (FAC) or systolic LA area, were not significantly increased in patients with abnormal PTFV 1 ( Table 1 ), indicating that the magnitude of PTFV 1 more likely reflects electrical but not structural remodeling as published previously [ 19 ].…”
Section: Resultssupporting
confidence: 59%
See 4 more Smart Citations
“…The LV EF was mildly reduced in both groups but worse in patients with abnormal PTFV 1 (43.15 ± 11.51% vs. 48.93 ± 7.45%, p = 0.035). Interestingly, volumetric parameters for LA size and function, such as LA fractional area change (FAC) or systolic LA area, were not significantly increased in patients with abnormal PTFV 1 ( Table 1 ), indicating that the magnitude of PTFV 1 more likely reflects electrical but not structural remodeling as published previously [ 19 ].…”
Section: Resultssupporting
confidence: 59%
“…In the current study, we observed significantly higher NT-proBNP levels at discharge and lower LV EF in the group with abnormal PTFV 1 , which may contribute to impaired atrial function and abnormal PTFV 1 . In accordance, we recently demonstrated a significant negative correlation between functional LA parameters, such as LA conduit and reservoir function, as measured by feature-tracking (FT) strain analysis of cardiac magnetic resonance (CMR) images, and the extent of PTFV 1 [ 19 ]. In contrast to atrial strain, volumetric MRI parameters for LA function such as systolic LA area or LA FAC did not show a significant association with PTFV 1 in the present study, which agrees with previous studies [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations